Can pharmacological receptor tyrosine kinase inhibitors sensitize poor outcome breast tumors to immune-based therapies? - Ursini-Siegel, Josie (Frontiers in Oncology, 2013)
Receptor tyrosine kinases are known to drive breast cancer progression, particularly in HER2 and basal tumors, the two worst prognosis subtypes. Tumour cells recruit host stromal components, including immune cells, which strongly influence disease progression. This has been studied in human breast cancer and translated to murine models of breast cancer. Stromal immune components including cytotoxic T lymphocytes (CTL) and natural killer (NK) cells, destroy cancer cells through a process termed immune surveillance. Unfortunately, clinically-detectable tumors escape these immune protective effects through their ability to limit the infiltration, activation and/or survival of CTLs in breast tumors. The immunosuppressed state of established tumors limits the success rate of immune-based therapies, and possibly other therapeutic modalities that depend on host immunity. Published studies demonstrate that receptor tyrosine kinases (RTK) facilitate breast cancer progression, in part, by establishing immune suppression. This raises the intriguing possibility that pharmacological RTK inhibitors may be exploited to sensitize breast cancer patients to immune-based therapies.